Relation entre perceptions paysannes de la variabilité climatique et observations climatiques au Sud-Bénin - Ulrich C.S. Y. Allé; Pierre V. Vissoh; Hervé Guibert; Euloge K. Agbossou; Abel A. Afouda (VertigO)
The study aims at analyzing farmers’ perceptions of climate variability and their relevance to climate observations. Climatic data from 14 stations and farmers’ perceptions of climatic variability were collected from 201 farm managers in 67 villages in southern Benin. A combination of qualitative (informal and semi structured interviews of socio-professional groups, participant observation and triangulation) and quantitative (Structured questionnaire) approaches were used. Farmers are more sensitive to changes in rainfall patterns from 1951 to 1970 and from 1971 to 1990, particularly the shift in the onset and the end of rainy seasons, increase in the frequency of drought sequences, decrease in the number of rainfall days and rainfall deficit than the relative recent increase in precipitations that occurred in 1990 and 2000 in the study area. However, shift in scale regional or local reduce significantly the gap between farmers’ perception and climatic data. Farmers also acknowledge the decrease in temperature and the raise in the frequency of violent winds during rainy seasons. These perceptions are in contradiction with climatic data collected and suggest in depth investigations to better understand these divergences. In order to mitigate climatic variability, farmers have developed adaption strategies mostly based on their perception. This offers window of perspectives to develop adaptation strategies based on farmers’ perception and interests.